2014
DOI: 10.7314/apjcp.2014.15.18.7731
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate Reductase Gene Germ-Line C677T and A1298C SNPs are Associated with Colorectal Cancer Risk in the Turkish Population

Abstract: Colorectal cancer (CRC) is the third most common cause of death due to cancer in the worldwide and the incidence is also increasing in Turkey. Our present aim was to investigate any association between germ-line methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and CRC risk in Turkey. A total of 86 CRC cases and 212 control individuals of the same ethnicity were included in the current study. Peripheral blood-DNA samples were used for genotyping by StripAssay technique, based on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…Nevertheless, for the sake of looking for possible reasons that might lead to such result, we performed heterogeneity analysis and tested publication bias. According to these results, 13 studies were excluded [ 29 31 , 40 , 43 , 47 , 48 , 52 , 55 , 61 , 63 , 77 , 107 ], the P -value was estimated to be 0.824, and the fixed effect model was applied. Ultimately, the results demonstrated that the rs1801133 polymorphism was significantly correlated with the risk of CRC ( Figure 2 ) (dominant model: OR =0.96, 95% CI =0.94–0.99; recessive model: OR =0.90, 95% CI =0.83–0.96; homozygous model: OR =0.88, 95% CI =0.82–0.95; allele model: OR =0.95, 95% CI =0.93–0.98).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, for the sake of looking for possible reasons that might lead to such result, we performed heterogeneity analysis and tested publication bias. According to these results, 13 studies were excluded [ 29 31 , 40 , 43 , 47 , 48 , 52 , 55 , 61 , 63 , 77 , 107 ], the P -value was estimated to be 0.824, and the fixed effect model was applied. Ultimately, the results demonstrated that the rs1801133 polymorphism was significantly correlated with the risk of CRC ( Figure 2 ) (dominant model: OR =0.96, 95% CI =0.94–0.99; recessive model: OR =0.90, 95% CI =0.83–0.96; homozygous model: OR =0.88, 95% CI =0.82–0.95; allele model: OR =0.95, 95% CI =0.93–0.98).…”
Section: Resultsmentioning
confidence: 99%
“… These 13 studies by Ozen et al, Ashmore et al, Delgado-Plasencia et al, Zhu et al, Prasad et al, Komlosi et al, Karpinski et al, Naghibalhossaini et al, Fernández-Peralta et al, Awady et al, Haghighi et al, Jin et al, Ryan et al were removed [ 29 , 30 , 31 , 40 , 43 , 47 , 48 , 52 , 55 , 61 , 63 , 77 , 107 ]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A associação entre os polimorfismos da MTHFR e o CCR tem sido estudada extensivamente, e vários fatores têm influenciado a relação entre as variáveis MTHFR e o risco de câncer 37 . Recentes literaturas mostram que parâmetros etiológicos tais como, mutações pontuais cromossômica, polimorfismos do gene, fatores ambientais, estilo de vida e alterações epigenéticas pode causar CCR, o status do folato também foi relatado como risco de CCR 38 .A diminuição da função da enzima MTHFR pode causar hipometilação do DNA devido a falta de fonte de metila intracelular e iniciar o processo carcinogênico38 .Há resultados conflitantes na literatura que dizem ter forte ligação ou nenhuma associação entre estes polimorfismos com o risco de CCR 33 .Elevados níveis de homocisteína estão também associados ao desenvolvimento de doenças neurológicas 33 .Indivíduos com variações genéticas nesta viade metilação e disfunção na regulação da metilação do DNA, tem um problema com o processamento de agentes tóxicos ambientais como a poluição do ar , muito comum nos dias atuais, causando danos à via de metilação semelhante a causada pelo tabagismo 33 . Recentemente evidências crescentes indicam, que o álcool pode induzir alterações epigenéticas, em particular os padrões de metilação do DNA, que também podem ser um fator importante para carcinogênese induzida pelo álcool 32 .…”
unclassified